Short-Term Outcomes of Elective High-Risk PCI with Extracorporeal Membrane Oxygenation Support: A Single-Centre Registry - Alexander M. Griffioen; Stijn C. H. Van Den Oord; Marleen H. Van Wely; Gerard C. Swart; Herbert B. Van Wetten; Peter W. Danse; Peter Damman; Niels Van Royen; Robert Jan M. Van Geuns (Journal of Interventional Cardiology)
Background. If surgical revascularization is not feasible, high-risk PCI is a viable option for patients with complex coronary artery disease. Venoarterial extracorporeal membrane oxygenation (VA-ECMO) provides hemodynamic support in patients with a high risk for periprocedural cardiogenic shock. Objective. This study aims to provide data about short-term outcomes of elective high-risk PCI with ECMO support. Methods. A retrospective single-center registry was performed on patients with high-risk PCI receiving VA-ECMO support. The short-term outcome was defined as the incidence of major adverse cardiac events (MACE) during the hospital stay and within 60 days after discharge. Results. Between January 2020 and December 2021, 14 patients underwent high-risk PCI with ECMO support. The mean age was 66.5 (±2.5) and the majority was male (71.4%) with a mean left ventricular ejection fraction of 33% (±3.0). Complexity indexes were high (STS-PROM risk score: 2.9 (IQR 1.5–5.8), SYNTAX score I: 35.5 (±2.0), SYNTAX score II (PCI): 49.8 (±3.2)). Femoral artery ECMO cannulation was performed in 13 patients (92.9%) requiring additional antegrade femoral artery cannula in one patient because of periprocedural limb ischemia. The mean duration of the ECMO run was 151 (±32) minutes. One patient required prolonged ECMO support and was weaned after 2 days. Successful revascularization was achieved in 13 patients (92.8%). Procedural success was achieved in 12 patients (85.7%) due to one unsuccessful revascularization and one procedural death. MACE during hospital stay occurred in 4 patients (28.6%) and within 60 days after discharge in 2 patients (16.7%). Conclusion. High-risk PCI with hemodynamic support using VA-ECMO is a feasible treatment option, if surgical revascularization is considered very high risk. Larger and prospective studies are awaited to confirm the benefits of ECMO support in elective high-risk PCI comparing ECMO with other mechanical circulatory support devices, including coaxial left cardiac support devices and IABP. Trial Registration. This trial is registered with NCT05387902.